The Relationship between Job Crafting and Work Engagement in One of the Local Authorities in Malaysia - Izzati Mahat, Nur; Sarip, Azlineer (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the relationship between job crafting (task crafting, relational crafting, and cognitive crafting) and work engagement (vigor, dedication, and absorption) in a Malaysian context. This study is focused on public officers, and respondents of this research include 79 middle managers at one of the local authorities in Malaysia. The hypothesis of this study was tested using Pearson Correlation Coefficient Analysis. Both mean levels of job crafting and work engagement were high, with 4.66 and 4.64, respectively. Therefore, it is proven that the middle managers agreed and practiced both job crafting and work engagement. In addition, the results also revealed that job crafting is positively and significantly related to work engagement, where p=0.000 (p<0.05) and r=0.712. Hence, the result implies that organizations should be paying more attention to the fact that job crafting and work engagement are related to one another and their benefits may help the organization to be more competitive and more successful in the future.